"There Are Many of Us": Online Testimonies From "Pill Victims" as a New Form of Health Activism. (June 2023) - Turrini, Mauro
The French pill scare is usually presented as a "media debate" triggered by the case of Marion Larat, a young woman who suffered a stroke attributed to the pill she was taking. This article intends to focus on a practice that preceded, accompanied, and followed this health scare: the publication of online testimonies of thrombotic reactions posted on the website of the French Association of Victims of Pulmonary Embolism and Stroke Associated with Hormonal Contraception (Avep). Through a discourse analysis, we intend to analyze these online public self-reports as an activist practice aimed at criticizing the dominant medical discourse on contraception. Four discursive frames emerged: unpreparedness of women and doctors, denial of blame and search for the cause, breaking the silence and building solidarity, and collective action. The first two frames concern the process women put in place to obtain the right to speak about and criticize a medical practice. The right to speak is achieved through a concise narrative style focusing on facts, bodily manifestations, and risk factors. The second pair refers to the formation of pill victims as subjects with an ambivalent status and ephemeral agency. The testimonies build what we call "lone solidarity", that is, the creation of a social bond and action around a common experience of witnessing medical injustice that develops without any exchange between members. This proves to be inclusive and viral, but at the same time fiercely anti-representational with respect to political struggles or social identification.